THE EFFECT OF ADMINISTRATIVE MANAGEMENT AND SERVICE QUALITY ON MEMBER LOYALTY WITH SATISFACTION AS A MEDIATION VARIABLE IN THE RED AND WHITE SUNTER AGUNG VILLAGE COOPERATIVE - Devia Aura; Leni Hartati (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study aims to analyze the effect of administrative management and service quality on member loyalty, with member satisfaction as a mediating variable in the Merah Putih Sunter Agung Village Cooperative. This study employs an explanatory quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The sample consisted of 176 cooperative members selected through total sampling. Data were collected using a five-point Likert scale questionnaire and analyzed through measurement and structural model evaluation. The results show that administrative management and service quality have a positive and significant effect on member satisfaction and member loyalty. Member satisfaction also has a positive and significant effect on member loyalty and partially mediates the effects of administrative management and service quality on member loyalty. The novelty of this study lies in integrating administrative management and service quality within a single mediation model and applying it to the Merah Putih Village Cooperative as a new-generation cooperative established under Presidential Instruction No. 9 of 2025. The findings emphasize that strengthening administrative governance and service quality is essential for enhancing member satisfaction, loyalty, and active participation